Non-fullerene organic solar cells based on diketopyrrolopyrrole polymers as electron donors and ITIC as an electron acceptor. Issue 11 (7th March 2017) - Jiang, Xudong; Xu, Yunhua; Wang, Xiaohui; Wu, Yang; Feng, Guitao; Li, Cheng; Ma, Wei; Li, Weiwei
Abstract : Non-fullerene organic solar cells based on diketopyrrolopyrrole polymers as electron donors andITIC as an electron acceptor were studied to show power conversion efficiencies of 4% with external quantum efficiencies above 0.4. Abstract : In this work, we provide systematic studies on the non-fullerene solar cells based on diketopyrrolopyrrole (DPP) polymers as electron donors and a well-known electron acceptorITIC .ITIC has been widely reported in non-fullerene solar cells with high power conversion efficiencies (PCEs) above 10%, when it is combined with a wide band gap conjugated polymer, while its application in small band gap DPP polymers has never been reported. Herein, we select four DPP polymers containing different thienyl linkers, resulting in distinct absorption spectra, energy levels and crystalline properties. Non-fullerene solar cells based on DPP polymers as donors andITIC as an acceptor show PCEs of 1.9–4.1% and energy loss of 0.55–0.82 eV. The PCEs are much lower than those of cells based on fullerene derivatives due to the poor miscibility between the DPP polymers andITIC, as confirmed by the morphology and charge transport investigation. The results indicate that it is important to tune the miscibility between the donor and acceptor in order to realize optimized micro-phase separation, which can further enhance the performance of DPP polymer based non-fullerene solar cells.